Same Call, Different Men : The Evolution of the Priesthood since Vatican II - Gautier, Mary L., 1952- (Book collections on Project MUSE., 2012)
Far-reaching changes continue to take place in the American priesthood. Building on insights gained from four previous surveys, Same Call, Different Men uses fresh data from a 2009 survey--jointly implemented by the National Federation of Priests' Councils and the Center for Applied Research in the Apostolate--in which nine hundred priests shared attitudes and stories about their lives and ministry. Among topics covered are the challenges of ministry with fewer ordinations and larger parishes, ministering to an increasingly multicultural laity, collaboration with lay leaders, and personal reflections on the sexual abuse issue. It also relates the many satisfactions of being a priest, one who brings Christ to others and who is invited into many profound moments of individual lives. - back cover.